Statistical analysis of the relationship of the enterprise indicators of capital use efficiency and the profitability - Chernata, T. (Економічний вісник Донбасу, 2016)
The article proposed the use of statistical methods in order to establish and analyze the relationship between indicators of industrial enterprises’ capital use efficiency and profitability. Effective and factorial indexes were used for analysis. We used Spearman rank correlation coefficient for establishing the preliminary tightness and direction of relationship between indicators. Methods of correlation - regression analysis, allowing to form the equations and multiple regression, which make up the capacious information to adopt and inform decisions in the field of financial management, were also applied